Elastin structure and its involvement in skin photoageing - Weihermann, A. C.; Lorencini, M.; Brohem, C. A.; Carvalho, C. M. (International journal of cosmetic science, 2017)
Skin aging is a complex process that may be caused by factors that are intrinsic and extrinsic to the body. Ultraviolet (UV) radiation represents one of the main sources of skin damage over the years and characterizes a process known as photoaging. Among the changes that affect cutaneous tissue with age, the loss of elastic properties caused by changes in elastin production, increased degradation and/or processing produces a substantial impact on tissue esthetics and health. The occurrence of solar elastosis is one of the main markers of cutaneous photoaging and is characterized by disorganized and non‐functional deposition of elastic fibers. The occurrence of UV radiation‐induced alternative splicing of the elastin gene, which leads to inadequate synthesis of the proteins required for the correct assembly of elastic fibers, is a potential explanation for this phenomenon. Innovative studies have been fundamental for the elucidation of rarely explored photoaging mechanisms and have enabled the identification of effective therapeutic alternatives such as cosmetic products. This review addresses cutaneous photoaging and the changes that affect elastin in this process. Résumé Le vieillissement de la peau est un processus complexe qui peut être causé par des facteurs intrinsèques et extrinsèques du corps. Les rayons ultraviolets (UV) représentent l'une des principales sources de dommages de la peau au fil des ans et caractérise un processus connu sous le nom de photo‐vieillissement. Parmi les changements qui affectent le tissu cutané avec l’âge, la perte des propriétés élastiques causées par des changements dans la production d’élastine, augmentation de la dégradation et / ou le traitement, produit un impact important sur l'esthétique et la santé des tissus. La survenue d'une élastose solaire est l'un des principaux marqueurs de photo‐vieillissement cutané et se caractérise par un dépôt désordonné et non‐fonctionnel des fibres élastiques. L'apparition d'un épissage alternatif du gène de l’élastine induit par le rayonnement UV, ce qui conduit à une synthèse insuffisante des protéines nécessaires à l'assemblage correct des fibres élastiques, est une explication possible de ce phénomène. Des études novatrices ont été fondamentales pour l’élucidation des mécanismes de photo‐vieillissement rarement explorés et ont permis l'identification d'alternatives thérapeutiques efficaces, tels que les produits cosmétiques. Cette revue porte sur le photo‐vieillissement cutané et les changements qui affectent l’élastine dans ce processus. Skin ageing is a complex process caused by factors that are intrinsic and extrinsic to the body, and loss of elastic properties produces a substantial impact on tissue aesthetics and health. Solar elastosis is one of the main markers of cutaneous photoageing, but the molecular mechanisms associated with solar elastosis are still unclear. UV radiation‐induced alternative splicing of the elastin gene and it is linked to photoageing and cosmetics.